MAGNETIC-PROPERTIES OF BCC CO FILMS - Bland, J; Bateson, R; Riedi, P; Graham, R; Lauter, H; Penfold, J; Shackleton, C (1991)
The magnetic properties of epitaxial bcc Co films of thickness 10-100 Å have been investigated using the surface magneto-optic Kerr effect (SMOKE), polarized neutron reflection (PNR), and nuclear magnetic resonance (NMR). The in-plane coercivity is found to vary strongly with thickness and a large magnetocrystalline anisotropy develops in-plane at 60 Å which is maintained in thicker films. PNR measurements on a Au-coated 100-Å bcc Co film at 300 K are consistent with a layer averaged magnetic moment per atom of 1.4 μB and a magnetization profile within 50 Å of the GaAs interface. NMR measurements on a 75-Å bcc Co film at 4.2 K yield the center frequency consistent with a moment per atom of 1.4 μB.